Cavernous haemangioma of spleen: a rare case report - Makde, Manjiri Milind; Rajdeo, Roma N.; Umap, Pradeep S.; Shrikhande, Anuradha V. (International Journal of Research in Medical Sciences, 2017)
Tumours of the spleen are as such rare. Of these rare tumours, haemangioma is the most commonly encountered benign tumour with fewer than 100 cases reported. It is either an incidental finding or presents as splenic enlargement or with complications. Preoperative investigations are often inconclusive and may not distinguish between haemangioma and metastases. We report a case of 40 years female with cavernous haemangioma of spleen presenting as massive splenomegaly. Splenic haemangioma presenting as massive splenomegaly is extremely rare and deserves a mention.